The evolution and development of waqf institution in a secular state: The Philippine case - Gamon, Alizaman Dumangcag; Tagaranao, Mariam Saidona (IIUM PRESS, 2017)
The relationship between state and Islamic institutions in secular society is a relatively new research area, complicated by the arguably secular worldview of main- stream development theory and practice. However, the establishment of waqf (pl. awqāf; sing. waqf) institutions or inalienable Muslim endowments in the Philippines can be traced back prior to colonialism in the Philippines. The waqf or endowment is deemed part of the Islamic law introduced and interwoven to the old folk’s traditions in the Philippines. The study analyzes the history and legal position of waqf institution and its implication towards the transformation of Muslim communities in the Philip- pines. The study evaluates the effectiveness of the remedies and solutions in addressing the challenges and problems of awqāf properties in Lanao del Sur, Philippines. The study is exploratory by its nature. The researcher opts to utilize qualitative method of gathering data. The flexibility and objectivity of the method allows the researcher to appreciate well-grounded descriptions and explanations of unforeseen thought, and their implications for the management and development of waqf in the Philippines. Waqf literatures in the Philippines have cursorily addressed the impact of government policies on the target population in the Autonomous Region in Muslim Mindanao (ARMM) and the grassroots response to the development of Islamic institutions, particularly awqāf properties. This research recommends the promulgation of a meaningful legal frame- work that guarantees the establishment of credible waqf-based model in management and financing which will then provide a strong support in the establishment of health clinic, Islamic religious centers and educational institutions.